ТЕОРЕТИЧНІ ОСНОВИ ЗАБЕЗПЕЧЕННЯ СУЧАСНОГО РОЗВИТКУ РЕГІОНІВ - Blagodarnyi, O.I.; Korshykova, I.O.; Pluzhnykova, E.A. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2015)
Basic definitions of the development of strategies for socioeconomic development are considered, and their main elements and characteristics as well. The features of the use of strategic planning methods are formulated including multilevel systems. REFERENCES